Representasi Identitas Transgender dalam Film Lovely Man (2011) - Utari, Anisah; Hapsarani, Dhita (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
Gender identity is understood by most people as limited to male and female sex. Conventional society has limitations in accepting gender diversity outside heteronormativity, leading to stigmatization and discrimination of transgender people. This research aims to analyze Lovely Man (2011) in representing transgender identity through narrative and visualization. This research uses narrative and visual text analysis methods by using Judith Buttler's gender perfomativity theory. The concept of gender in this study is analyzed based on character dialogue, gesture, and attitude. The results show that transgender individuals get double marginalization from society as transgender and commercial sex workers. The film Lovely Man (2011) shows that violence against transgender is seen as a form of threat to conventional society for behavior against traditional norms. The movie also shows the relationship between a transgender and a veiled woman who becomes pregnant out of wedlock, as a form of opposition to society's expectations of the veiled symbol. Thus, it can be concluded that Lovely Man (2011) attempts to show transgender from another perspective.